Socialization of Higher Education as a Means in Increasing Participation of High School / Vocational Students equally in the Pandemic Period - Innayatul Laili; Yuniar Mujiwati; Achmad Sukron Firmansyah; Aditya Firmansyah; Siti Afifah (TRIDARMA: Pengabdian Kepada Masyarakat (PkM), 2022)
One of the compulsory courses of Real Work From Home in increasing community participation in universities, which is implemented by PGRI Wiranegara University as an obligation of community service and service to the community is also one of the government programs. This form of devotion is an effort to reach the wider community amid the limitations and ferocity of the covid-19 pandemic. In addition, the purpose and purpose of this devotion is done to provide knowledge and insight to high school students who will graduate and want to continue to the level of higher education. Not only that this devotion also has another goal that is to support government programs in preventing the spread of the crona virus which to this day has not disappeared. The support is manifested in the socialization of health protocols to high school students as equals. This devotion is done with an online system or commonly called the internet network so that it can meet virtually.